Social protection as a right of people affected by tuberculosis: a scoping review and conceptual framework - Melisane Regina Lima Ferreira; Rafaele Oliveira Bonfim; Pedro Augusto Bossonario; Venisse Paschoalin Maurin; Ana Beatriz Marques Valença; Paula Daniella de Abreu; Rubia Laine de Paula Andrade; Inês Fronteira; Aline Aparecida Monroe (BMC, 2023)
Abstract Background Tuberculosis is an infectious disease strongly influenced by social determinants closely associated with cycles of poverty and social exclusion. Within this context, providing social protection for people affected by the disease constitutes a powerful instrument for reducing inequalities and enhancing inclusion and social justice. This study aimed to identify and synthesize strategies and measures aimed at ensuring social protection as a right of people affected by tuberculosis. Methods This is a scoping review, with searches conducted in six databases in February 2023. We included publications from 2015 onwards that elucidate strategies and measures of social protection aimed at safeguarding the rights to health, nutrition, employment, income, housing, social assistance, and social security for people affected by tuberculosis. These strategies could be implemented through policies, programs, and/or governmental agreements in any given context. The data extracted from the articles underwent descriptive analysis and a narrative synthesis of findings based on the dimensions of social protection. Additionally, we developed a conceptual framework illustrating the organizational and operational aspects of measures and strategies related to each dimension of social protection identified in this review. Results A total of 9317 publications were retrieved from the databases, of which sixty-three publications were included. The study's results highlighted measures and strategies concerning the social protection of people affected by tuberculosis. These measures and strategies revolved around the rights to proper nutrition and nourishment, income, housing, and health insurance, as well as expanded rights encompassing social assistance and social welfare. It was reported that ensuring these rights contributes to improving nutritional status and the quality of life for individuals with tuberculosis, along with reducing catastrophic costs, expanding access to healthcare interventions and services, and fostering TB treatment adherence, thereby leading to higher rates of TB cure. Conclusions Our findings identify social protection measures as a right for people affected by tuberculosis and have the potential to guide the development of evidence-based social and health policies through collaboration between tuberculosis control programs and governmental entities.